Strategi Guru dalam Membentuk Karakter Siswa Melalui Pendidikan Karakter Siswa SDN 060914 Medan - Sitanggang, Rizka Pahmawati Regina; Simanjuntak, Sinta Dameria; Manullang, Six Martawati; Gurning, Riris (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
This study aims to determine the impact of character education on the character of students at SDN 060914 Medan. The approach in this study uses a quantitative descriptive approach with survey methods. The sampling technique uses a purposive sample, namely by taking samples from fifth grade students with a total of 20 students. The research instruments used were interviews, questionnaires, and observation. The results of the research show that students' behavior in implementing character education which includes religious, honest, diligent, disciplined, and caring/responsible characters is in the pretty good category. As for the constraints on the lack of cooperation from parents to further foster students when they are at home, as well as their daily social environment. So the solution to these obstacles is to hold meetings with parents at the end of each semester.